The Long-term Effects of Iron Deficiency in Early Infancy on Neurodevelopment - Korczak, Anna; Wójcik, Emilia; Olek, Ewa; Łopacińska, Olga; Stańczyk, Katarzyna; Korn, Aleksandra; Jędrzejczyk, Justyna; Szewczyk, Oliwia; Burda, Katarzyna; Czarnecka, Karolina (Journal of Education, Health and Sport, 2024)
Introduction and Purpose: Iron deficiency alongside anaemia is one of the most significant global health concerns with potentially long-lasting implications on child development and health outcomes. The period of infancy represents a crucial phase of central nervous system maturation, rendering infants particularly susceptible to the adverse effects of iron deficiency. It is therefore crucial to pay close attention to this issue. The aim of this review is to elucidate the neurological implications of iron deficiency in infancy and emphasize the necessity of implementing preventive strategies to safeguard child development. State of Knowledge: Iron deficiency in infancy can result in impairments of brain development. Extensive research highlights the influence of this micronutrient on various physiological processes, including the synthesis of neurotransmitters, neuronal metabolism, myelination, synaptogenesis and gene expression. Furthermore, iron deficiency during infancy is associated with adverse developmental outcomes, including cognitive, motor, and socioemotional deficits. Long-term follow-up studies have elucidated the enduring neurological consequences of iron deficiency in infancy, with effects extending into childhood and beyond. Summary: Given that the changes that occur during the infantile period are often irreversible and have long-lasting implications for future development, it is of the utmost importance to prioritize prevention strategies.